Response of mononychellus tanajoa (acari: tetranychidae) to cropping systems, cultivars, and pest Interventions - Toko, M.; Yaninek, J.S.; O'Neil, R.J. (1996)
The effects of cropping systems (cassava monocropped and intercropped with maize), pest interventions (spray of acaricide and release of an exotic phytoseiid) and cultivars (‘Agric’ and ‘TMS 30572’) on the population dynamics of the green mite, Mononychellus tanajoa (Bondar), were evaluated in 2 locations (Dogbo and Intemational Institute of Tropical Agriculture) in Benin Republic, West Africa. Maize and cassava were intercropped at the beginning of the wet season. Pest interventions were applied during the dry season with Amblyseius manihoti Moraes (= limonicus s.l.) (Garman & McGregor) (Acari: Phytoseiidae) released at the beginning of the dry season at both sites and the acaricide dimethoate sprayed bimonthly at Dogbo and once in December at the International Institute of Tropical Agriculture. Intercropping cassava with maize had no significant effect on M. tanajoa and associated phytoseiid predator populations during the intercropping, dry, and postdry seasons. The acaricide spray reduced M. tanajoa densities 50% below those of the predator and the control (no predator and no spray) treatments. A. manihoti reduced M. tanajoa densities 20% below the control treatment by the end of the experiment. Agric supported 2–3 times more mites per leaf than did TMS 30572. A pest management strategy that combines resistant cultivars and an efficient exotic predator is suggested to control M. tanajoa .